Deficient AMPK-SENP1-Sirt3 signaling impairs mitochondrial complex I function in Parkinson’s disease model - Xiaoyu Sun; Jianyi Shen; Yimei Shu; Tianshi Wang; Lu He; Ruinan Shen; Yifan Zhou; Jinke Cheng; Suzhen Lin; Jianqing Ding (Translational Neurodegeneration)
Abstract Background Epidemiological studies have revealed increased Parkinson’s disease (PD) risk among individuals exposed to pesticides like 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). MPTP is frequently used to induce PD-like symptoms in research models by disrupting mitochondrial complex I (CI) function and causing dopaminergic neuronal loss in the nigrostriatal region. However, the pathway(s) through which MPTP impairs mitochondrial CI function remain to be elucidated. In this study, we aim to identify the molecular mechanisms through which MPTP modulates CI function and define the specific subunits of mitochondrial CI affected by MPTP. Methods Male mice encompassing either wild-type Sirt3 or Sirt3 K223R de-SUMOylation mutation, were intraperitoneally injected with either MPTP or saline. In vitro experiments were conducted using the SH-SY5Y cell line with or without the Sirt3 de-SUMOylation mutation. Movement performance, mitochondrial function, and protein acetylation were evaluated. Results MPTP exposure, both in vitro and in vivo, disrupted the AMPK–SENP1–Sirt3 axis, leading to impairment of mitochondrial function. Specifically, MPTP suppressed activation of AMPK, impeding the entry of SENP1 into the mitochondria. The lack of mitochondrial SENP1 resulted in increased levels of SUMOylated Sirt3, which inhibited its deacetylase activity. This led to a significant increase in the acetylation of CI subunits NDUFS3 and NDUFA5, which resulted in reduced CI activity and inhibition of mitochondrial function, and eventually dopaminergic neuronal death. In this pathway, sustained deSUMOylation mutation of Sirt3 (K223R in mice, K288R in humans) mitigated the impact of MPTP on mitochondrial dysregulation, as well as dopaminergic neuronal death and behavioral deficits. Conclusion The disordered AMPK-SENP1-Sirt3 pathway plays a crucial role in the MPTP-induced CI dysfunction and PD-like phenotype, which provide valuable insights into the mechanisms of PD pathogenesis.